Formulação matemática para cálculo de variação de concentração em escoamento estacionário - Brandão, Waldo Hosternes Peixoto (2011)
The main aim of this research is to evaluate a variation of concentration between the affluent and effluent in a biophysical or physicochemical system. The theoretical system of references used here was based upon a differential equation of steady flow, involving a chemical kinetics and a longitudinal dispersion, in which there is a number of sufficiently low dispersion and efficiency, related to reactors. The chemical kinetics approached was of the Monod type, first order, any order and one which was set up similar to a Monod. We developed a new model of molecular decay which allowed the generation of new equations for steady flow. We obtained relationships between volumetric parameters and chemical kinetics of a perfect mixture of steady flow. In this study we found out about some similarities concerning the literature of chemical kinetics in a steady flow. It was also designed a study aiming to allow better scaling of the actual hydraulic retention time, reasonably proven by the surveyed sources.